Risk of infections in bispecific antibody therapy for multiple myeloma: a comprehensive review of literature - Fahad Alshammari; Abdullah M. Alrajhi; Jude Howaidi (Hematology)
Multiple Myeloma (MM) is a malignancy characterized by abnormal production of monoclonal immunoglobulins in plasma cells. Bispecific antibodies have emerged as a significant advancement in MM treatment, offering high effectiveness and specificity by targeting different antigens such as BCMA, CD38, and FcRH5. However, the risk of infection poses a major challenge in MM patients, which is thought to be influenced by various factors.The overall risk of infections associated with the use of BsAbs is estimated to be approximately 56% for all grades, with Grade 3/4 infections accounting for 24% of cases. Notably, BCMA-targeted BsAbs are associated with a higher incidence of infections compared to other targets. Risk factors contributing to infection occurrence include BsAbs risk of neutropenia and hypogammaglobulinemia as well as the inherent nature of the disease and patient-related factors. Bacterial infections, particularly respiratory tract and gastrointestinal infections are the most commonly reported, while viral infections such as CMV and rhinovirus are also prevalent in patients receiving BsAbs. Additionally, fungal infections have been documented in MM patients. Prophylactic measures for bacterial and fungal infections are tailored based on individual patient risk assessments, while viral infection prophylaxis is recommended for all refractory/relapsed MM patients receiving BsAbs.